Variabilidade espacial e temporal da qualidade das águas no trecho perenizado na Bacia Hidrográfica do Curu, Ceará - Frota Júnior, José Itamar (2006)
This research aims analyze the spatial and temporal variability in quality of the water used to perennialized area the hydraulic basin of river Curu, Ceara state, Brazil, evaluating the effects of the anthropic action and the influence of the different types of soils in the region. The following parameters were appraised: cations (Ca2+, Mg2+, Na+, K+), anions (HCO3 -, Cl-) and also: SAR, electric conductivity, pH and dissolved solids. During a period of one year, samples of water were collected in nine points distributed along the perennialized part of the basin of Curu and were analysed in the Soils and Water Laboratory at Federal University of Ceara State. Spatial and temporal variability were considered in the analysis of the medium values of the parameters. Spatial variability was appraised using the Analysis of Variance to 5% and the comparison of the averages with the Test of Tukey to 1%. Regarding the temporal variability, the medium values of the periods dry and rainy were compared and analyzed, in order to classificate waters using the Diagram of Piper. The results evidenced increment of salts along the basin. In the point 1 (Serrota-Pentecoste) the medium value found for sodium was of 1,92 mmolc L-1, while in the point 9 (Pedras Farm-Paraipaba) it was of 3,47 mmolc L-1. It was clear the anthropic influence in the quality of the water studied along the whole basin. The most significant differences in the parameters were observed among the points P1, P2 and P3 in the middle part of the basin of Curu, and P8 and P9 in the low part of the basin, where from the point 6, the river receives waters of drainage of irrigated perimeters and effluents of sewers. In respect of seasonality, an increment in the medium values was observed in the rainy period, justified for the increase of superficial drainage and wash of the salts, originated from the irrigated perimeters located in the basin. With the results of the analysis, the studied waters were classified as chlorinated.